2019
DOI: 10.2174/1573396315666181126105812
|View full text |Cite
|
Sign up to set email alerts
|

Human Breast Milk-acquired Cytomegalovirus Infection: Certainties, Doubts and Perspectives

Abstract: Breast Milk (BM) is the best source of nutrition for newborns, especially if premature. In fact, its beneficial impact on short- and the long-term neonatal outcome has was deeply described.Unfortunately, BM could not be always so safe, especially due to the possible presence of maternal viruses that can be shed and transferred to the breastfed neonate. Among these, Cytomegalovirus (CMV) can potentially lead to a serious and acute illness, mostly in case of low gestational age.Some studies also report the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 130 publications
(349 reference statements)
2
85
4
3
Order By: Relevance
“…The estimated incidence of congenital CMV infections varies in developed and developing countries with rates in all live births ranging from 0.6 to 0.7% compared to a range between 1 and 5%, respectively. The high rates of estimated incidence in developing countries are associated with the high rates of maternal seroprevalence in these countries (5). The rate of congenital CMV infection from our country was reported as 0.2% (12).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The estimated incidence of congenital CMV infections varies in developed and developing countries with rates in all live births ranging from 0.6 to 0.7% compared to a range between 1 and 5%, respectively. The high rates of estimated incidence in developing countries are associated with the high rates of maternal seroprevalence in these countries (5). The rate of congenital CMV infection from our country was reported as 0.2% (12).…”
Section: Discussionmentioning
confidence: 61%
“…Infection acquired during the intrapartum period from maternal cervical secretions or in the postpartum period from human milk is not usually associated with clinical illness in term infants. In preterm infants; however, postpartum infection resulting from human milk or from transfusion from CMV-seropositive donors has been associated with hepatitis, interstitial pneumonia, hematologic abnormalities including thrombocytopenia and leukopenia, and a viral sepsis syndrome (5,6). Antiviral therapy with ganciclovir and/or valganciclovir has been reported to be beneficial for improving neurodevelopmental sequelae and hearing outcomes of congenital CMV infection; however, treatment outcomes are not well reported (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, metabolomics could describe maternal and fetal status in congenital HCMV infection, allowing an early diagnosis and an accurate management [34], and, in our opinion, it could be also applied in the evaluation of breast milk acquired CMV infection [35].…”
Section: Metabolomics In Obstetricsmentioning
confidence: 87%
“…BM is the best source of nutrition for neonates. The American Academy of Pediatrics has reported that BM feeding is very important for babies ≤6 months old, and BM is irreplaceable, particularly in premature infants; thus, CMV infections via BM are worthy of research attention …”
Section: Introductionmentioning
confidence: 99%
“…The American Academy of Pediatrics has reported that BM feeding is very important for babies ≤6 months old, and BM is irreplaceable, particularly in premature infants; thus, CMV infections via BM are worthy of research attention. 7,8 As a common disease during the neonatal period, neonatal jaundice is mostly a physiological phenomenon during the normal growth process, but is occasionally a clinical manifestation of some latent disease.…”
Section: Introductionmentioning
confidence: 99%